Considerations to the entrepreneurship formation: Exploring new domains and possibilities (2010)
Entrepreneurship has long been exclusively associated with the business sphere, but despite efforts on the part of educational institutions, development centers, and government agencies, it has had a remarkably poor development on other dimensions such as on the public and social spheres. This article proposes a reflection regarding the importance of entrepreneurship for an efficient and competitive corporate development based on different concepts adopted during past decades for the purpose of stressing its transdisciplinary nature. Then it goes on with a review of experiences to explore new possibilities for its application. Lastly, it raises awareness for people to have an open mindset to new dimensions of life in a society. © 2010 Universidad Icesi. All rights reserved.